2015
DOI: 10.1007/s11664-015-4121-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ni on the Formation and Growth of Primary Cu6Sn5 Intermetallics in Sn-0.7 wt.%Cu Solder Pastes on Cu Substrates During the Soldering Process

Abstract: This paper investigates the effect of 0.05 wt.% Ni on the formation and growth of primary Cu6Sn5 in Sn-0.7 wt.%Cu solder paste soldered on a Cu substrate, using a real-time synchrotron imaging technique. It was found that small additions of Ni significantly alter the formation and growth of the primary Cu6Sn5 intermetallics, making them small. In contrast, without Ni, primary Cu6Sn5 intermetallics tend to continue growth throughout solidification and end up much larger and coarser. The primary effect of the Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 34 publications
(30 reference statements)
3
27
0
Order By: Relevance
“…The experimental set-up was similar to previous research [7,10,[21][22][23] and a 21 keV beam was used. The transmission imaging field of view was 877 m x 658 m (1920x1440 pixels) with a resolution of 0.457 m per pixel.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The experimental set-up was similar to previous research [7,10,[21][22][23] and a 21 keV beam was used. The transmission imaging field of view was 877 m x 658 m (1920x1440 pixels) with a resolution of 0.457 m per pixel.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…It has also been reported by Zeng et al (2014) that Ni additions to Sn0.7Cu solder alloys suppress the Cu3Sn layer intermetallic layer which typically forms between the Cu6Sn5/Cu interface as a result of continuous Cu diffusion from the substrate into the Cu6Sn5 layer. Besides the suppression of the intermetallic layer, Mohd Salleh et al (2016a) revealed that primary Cu6Sn5 in the bulk could be significantly refined with Ni additions. In Sn-Ag-Cu solders, additions of Ni were reported by Chuang and Lin (2003) to also effectively suppress the Cu6Sn5 layer.…”
Section: Introductionmentioning
confidence: 99%
“…The real time observation experiments were performed at BL20XU beamline in the SPring-8 synchrotron using an in-situ synchrotron X-ray real time solidification observation setup developed in previous research [39][40][41][42]. The parameters were chosen to allow a high degree of coherence, absorption contrast and phase contrast enabling boundaries in the sample to be …”
Section: Synchrotron X-ray Radiography Imagingmentioning
confidence: 99%